A gamification framework as a collaboration motivator for software development teams - Castro, Flávio Steffens de (2016)
Gamification is the use of game elements in non-game context to motivate people to achieve goals. Its use is becoming very popular in software development organizations due to work being based upon human-centric and brain-intensive activity. This research presents a framework that identifies common collaboration issues that affect software development teams and how to apply game elements to mitigate them by jump starting behavior change. The framework is defined based on literature and on a field study with gamification and software development professionals. In its preliminary evaluation with practitioners and specialists, they presented evidences of the applicability of this framework as a motivator to foster collaboration in software teams. The framework can be used by management to promote behavioral change in their industrial teams and by researchers to advance the state of the art in collaboration in the field. Tool designers can also benefit from it by having access to the comprehensive and compiled body of knowledge to inspire them to design new tools or improve current ones to support collaboration in software teams.